Exopolymer particles: microbial hotspots of enhanced bacterial activity in Arctic fast ice (Chukchi Sea) - Klaus Meiners; Krembs, C; Gradinger, R (2008)
Sea ice is an important structuring element of Arctic marine ecosystems and provides a vast low-temperature habitat for ice-associated bacteria. While it is now known that sea ice sequesters large amounts of extracellular polymeric substances (EPS) contributing significantly to its particulate organic carbon pool, the ecological role of EPS in sea ice is poorly understood. Using in situ incubations combined with a newly developed triple-staining method (Alcian Blue, DAPI, CTC), we determined the number of CTC-reducing (i.e. actively respiring) sea-ice bacteria living freely or attached to gel-like exopolymer particles. Samples were collected at 6 depths from Chukchi Sea coastal fast ice in April, May and June 2003. Concentrations of exopolymer particles ranged between 1.8 × 106 and 149.1 × 106 particles l–1 (average 4.7 × 106 particles l–1) and showed strong vertical gradients with maximum concentrations at the ice-water interface. Total bacterial numbers (TBN) ranged from 0.18 × 109 to 8.48 × 109 cells l–1 with an average fraction of 7.4% of actively respiring cells (range 3.0 to 17.2% of TBN). The attached bacterial fraction (range 4.6 to 28.5%, average 15.0% of TBN) showed a significantly, approximately 4 times higher proportion of actively respiring cells (average 19.6%, range 7.8 to 37.6%) when compared to the free-living fraction that had an average of 5.4% (range 1.1 to 11.2%) of actively respiring cells. In conclusion, exopolymer particles in sea ice are microbial hotspots of increased bacterial activity able to foster enhanced biogeochemical cycling.